THE EFFECT OF ORGANIZATIONAL CULTURE, EMPLOYEE ENGAGEMENT, AND JOB SATISFACTION ON EMPLOYEE ORGANIZATIONAL COMMITMENT AT PT AEROFOOD ACS SURABAYA - Irawati , Ferdina; Firdaus , Vera; Prapanca, Detak (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Organizational commitment is critical for enhancing performance and long-term success, driven by key factors such as organizational culture, employee engagement, and job satisfaction. Specific Background: While these factors are widely studied, their combined effect on organizational commitment within the aviation catering industry has not been extensively examined, particularly in the context of PT Aerofood ACS Surabaya. Knowledge Gap: Limited research exists on how organizational culture, employee engagement, and job satisfaction interact to influence organizational commitment in this unique sector. Aims: This study aims to analyze the influence of organizational culture, employee engagement, and job satisfaction on organizational commitment among employees at PT Aerofood ACS Surabaya. Results: The findings reveal that employee engagement and job satisfaction have a significant and positive impact on organizational commitment, while organizational culture shows no significant effect. Engaged employees and those satisfied with their work environment, especially when supported by responsible colleagues, demonstrate higher organizational commitment. Novelty: Contrary to expectations, organizational culture did not significantly influence commitment, highlighting the stronger roles of engagement and job satisfaction. Implications: Organizations should prioritize fostering employee engagement and job satisfaction by creating a supportive work environment to enhance commitment levels. Expanding beyond traditional focus on culture may yield better outcomes for organizational loyalty.